Implementation of E-Warong Program - Abdillah Fajar; Isnaini Rodiyah (Indonesian Journal of Public Policy Review, 2022)
In the implementation of the BPNT program in Wonomlati Village in terms of standards and policy objectives it has not been effective enough, because there is still an inaccuracy in the target recipients of assistance, as well as the timeliness of aid delivery. The results of this study indicate that the measurement of the success of the implementation of the non-cash food assistance program in Wonomlati Village which is said to be effective is a resource indicator because the resources can run well because the service providers can help make it easier for the community to obtain good services, the characteristics of the implementing organization in this case can work. with unity and in the established procedures that are appropriate so that they can achieve the same goal, the attitude of the implementers in this e-warong program is good, this can be seen from the role of officers who are very selective in determining the people who receive the BPNT program, communication between organizations running quite well so that there is no difference in the data of BPNT recipients, and the socio-economic and political environment can be said to be effective because it can help the community's economy. While one indicator in the implementation of the non-cash food assistance program that has not been achieved is the standard indicators and policy targets, because there are still delays in receiving aid which causes confusion and queues in taking aid at the specified e-warong.